Analisis Gaya Pengasuhan Orang Tua terhadap Motivasi Belajar Siswa Tingkat Sekolah Menengah Atas - Rafiqi A’azzul Akrom; Anas Ahmadi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The aim of this research is to find out the impact of parents' parenting style on their children's learning motivation at the SMA/MA class XII Madrasah Aliyah Tarbiyatul Wathon Gresik school year 2024/2025. Using a descriptive qualitative approach. The sample in this study was 15 students from class XII MIPA. The data collection methods used were observation, interviews and documentation. This research reveals that parents use a variety of parenting styles. The majority of student parents tend to apply a democratic or authoritative parenting style, while only a few choose a permissive or authoritarian style. From this research, it was revealed that 13 parents used a democratic/authoritative parenting style, 1 parent used an authoritarian style, and 1 other parent used a permissive style. As a result, students whose parents used a democratic or permissive parenting style showed high learning motivation. On the other hand, students with low learning motivation usually come from families with an authoritarian parenting style. These findings confirm that parental involvement in choosing a parenting style greatly influences children's motivation to learn.